(untitled) (PANGEEA, 2025)
The wastewater from the ceramic industry contains a concentrated, white-coloured complex of substances in suspension due to the mineral content of most of the raw materials entering the production process, such as kaolin, clay, feldspar, sand, etc. The high turbidity of these waters often involves high costs. In this context, we investigated the efficiency for the removal of turbidity of two types of flocculants, namely aluminium polychloride and an emulsion of cationic polyacrylamide. Following laboratory-scale experiments, we achieved a 91.3% reduction in turbidity for the cationic polyacrylamide solution with a volume of 5 ml at a speed of 150 rpm and a shaking time of only 2 minutes, and 94.67% with polyacrylamide under similar conditions, after which the rate was reduced to 30 rpm for 20 min.